Cell imaging with multi-color DNA framework probes. Issue 86 (12th October 2021) - Xie, Mo; Guo, Linjie; Xing, Shu; Cao, Shuting; Zhao, Ziwei; Liang, Kaiyi; Li, Jiang; Luo, Shihua; Zhang, Yu; Wang, Lianhui
Abstract : FDF-encoded multi-color fluorescent probes incorporating different aptamer motifs for pattern recognition of different cell lines. Abstract : Utilizing the programmability of the fractal DNA frameworks, multi-color probes were constructed by arranging fluorescent molecules and nucleic acid aptamers on the structure. Multiplexed cell imaging and classification was realized through pattern recognition.